Can the household clean energy transition ameliorate health inequality? Evidence from China - Wu, Lili; Liu, Qin; Li, Lin (Frontiers in Public Health, 2024)
China is actively encouraging households to replace traditional solid fuels with clean energy. Based on the Chinese Families Panel Survey (CFPS) data, this paper uses propensity scores matching with the difference-in-differences model to examine the impact of clean energy in the household sector on residents' health status, and whether such an energy transition promotes health equity by favoring relatively disadvantaged social groups. The results show that: (1) The use of cleaner cooking fuels can significantly improve residents' health status; (2) The elderly and women have higher health returns from the clean energy transition, demonstrating that, from the perspective of age and gender, the energy transition contributes to the promotion of health equity; (3) The clean energy transition has a lower or insignificant health impact on residents who cannot easily obtain clean energy or replace non-clean energy at an affordable price. Most of these individuals live in low-income, energy-poor, or rural households. Thus, the energy transition exacerbates health inequalities. This paper suggests that to reduce the cost of using clean energy and help address key issues in health inequality, Chinese government efforts should focus on improving the affordability, accessibility, and reliability of clean energy.